Is Workload Associated with Ulnar Collateral Ligament Tears in Professional Baseball Players? An Analysis of Days of Rest, Innings Pitched and Batters Faced (126). Issue 10 (31st October 2021) - Chalmers, Peter; Mcelheny, Kathryn; Dangelo, John; Ma, Kevin; Rowe, Dana; Erickson, Brandon
Objectives: To determine if workload; as measured by number of days rest between outings, innings pitched, batters faced, and being a starting pitcher; associates with risk for sustaining a subsequent UCL tear in professional baseball players. Methods: All professional baseball pitchers who sustained a UCL tear between 2011-2017 were identified using the major league baseball (MLB) Health and Injury Tracking System (HITS). A separate player usage was used to determine workload . We then compared these variables between player-games 2, 6, 12, and >12 weeks prior to a documented UCL tear and player games from a non-UCL tear control group. In a paired analysis, we compared the acute workload (2, 6, 12 weeks) prior to injury and the injured player's workload >12 weeks prior to injury. Results: There were 2, 204 elbow injuries within MLB, 369 of which were unique UCL tears in pitchers. In all time periods, player-games with more days rest, more innings pitched, and more batters faced associated with a subsequent UCL tear. Players who pitched 4 of more innings per outing had a 1.78-fold increase in percent of players with a subsequent UCL tear as compared to players with one inning pitched. Being a starting pitcher carried a relative risk of 1.51 (p<0.001) of subsequent UCL injury. In a paired analysis there were significantly more innings pitched and batters faced in the player-games 2 weeks prior to UCL injury than in the player-games >12 weeks prior to UCL injury (p=0.028 and p=0.017). Conclusions: Being a starting pitcher, pitching more innings per game, and facing more batters per game increased the risk of a UCL tear. An increase in workload in the 2 weeks prior to injury over that player's baseline also significantly increased the risk for injury.